Numerical model analysis of subgrade settlement with foam mortar reinforcement based on thickness variation - Jusi, Ulfa; Pratikso, P; Maizir, Harnedi (Journal of Applied Engineering Science, 2024)
Soft soils have low bearing capacity characteristics and can cause high settlement. Sub grade which becomes the lowest layer in road construction is expected to have a strong bearing capacity so that it can carry the construction load on it. To overcome this problem, it is necessary to reinforce it. Problems will arise if the thickness of the soft soil in the subgrade varies. So, it needs to know and identify the scale of declining that occurs if the soft soil variation is reinforced on it. Foam mortar is an alternative reinforcement that is expected to improve the properties of the soft soil. The purpose of this research is to analyze the soft soil embankment model using foam mortar reinforcement against variations in soft soil height. The method of analysis was carried out by numerical method of Plaxis 2D version 2023. The geometric model in this study with foam mortar thickness of 30 cm was varied against subgrade layer height of 60 cm, 120 cm and 180 cm. The modeled load is a centralized load with variations of 0, 10, 20, 40, 60, 80, 100 and 120 kN. Numerical results obtained the highest settlement occurred at 180 cm soft soil layer of 0.01421 mm. The largest deformation occurred in the soft soil layer of 1,461 x 10-3 mm. In conclusion, the thicker the soft soil layer, the higher the settlement and the greater the deformation.